1992
DOI: 10.1017/s0003356100037570
|View full text |Cite
|
Sign up to set email alerts
|

A note on the apparent digestibility and nutritive value of whole cottonseed given to sheep

Abstract: Four castrated crossbred (Karagouniki♂ × Friesian♀) rams were used in a 4 × 4 Latin-square design to determine the apparent digestibility of four diets based on alfalfa hay and maize grain and containing varying proportions of whole cottonseed (WCS). The proportions of WCS studied were 0, 175, 355 and 530 g/kg diet dry matter (DM) and the respective apparent digestibility coefficients of DM were 0·744, 0·716, 0·689 and 0·625; of organic matter, 0·772, 0·739, 0·718 and 0·643; and of neutral-detergent fibre (NDF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
4

Year Published

1997
1997
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 5 publications
1
6
0
4
Order By: Relevance
“…These results differ from those of Luginbuhl et al (2000) who reported that, using 24% of cottonseed in the diet of Boer goats decreased DMI compared with a control group. However, the increase in DMI, observed in the present study, is consistent with the results of Karalazos et al (1992) who included 0, 17.5, 35.5 and 53.0% WCS in a diet for rams. Coppock et al (1987) stated that the DMI of dairy cattle did not change when up to 25% WCS was included in their diet.…”
Section: Resultssupporting
confidence: 92%
“…These results differ from those of Luginbuhl et al (2000) who reported that, using 24% of cottonseed in the diet of Boer goats decreased DMI compared with a control group. However, the increase in DMI, observed in the present study, is consistent with the results of Karalazos et al (1992) who included 0, 17.5, 35.5 and 53.0% WCS in a diet for rams. Coppock et al (1987) stated that the DMI of dairy cattle did not change when up to 25% WCS was included in their diet.…”
Section: Resultssupporting
confidence: 92%
“…Estes resultados são contrários aos relatados por Warren et al (1988), que forneceram 0; 25 e 50% de CAI, respectivamente, com 8, 1, e 12,6% de EE, e Karalazos et al (1992), que notaram depressão linear significativa no coeficiente de digestibilidade da MS e MO com o aumento do caroço de algodão de 0 a 53% na dieta. Também Zinn (1989) verificou diminuição linear da digestão ruminal da MO com aumento do nível de óleo como suplemento de 0 a 8%, o que pode ser creditado ao impacto da gordura na dieta, que pode deprimir a digestibilidade da fibra.…”
Section: Resultsunclassified
“…Smith & Vosloo (1990) também constataram aumentos na digestibilidade de EE nas dietas mais concentradas em caroço de algodão, fato também confirmado por Karalazos et al (1992), que observaram aumento linear da digestibilidade de EE com o aumento dos teores de CAI de 0,0 para 35,5% da dieta.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…As análises de fibra em detergente neutro, fibra em detergente ácido, hemicelulose e celulose seguiram o método seqüencial descrito por Van Soest (1991 Segundo Villela et al (1996), para vacas leiteiras, o consumo de fibra em detergente neutro não foi influenciado pela inclusão do caroço de algodão. Karalazos et al (1992) observaram que os coeficientes de digestibilidade da fibra em detergente neutro e fibra em detergente ácido foram maiores com a adição de 35,5% de caroço de algodão e declinaram quando a substituição foi de 53% de caroço de algodão (12% de óleo). Keele et al (1989) verificaram que o coeficiente de digestibilidade da fibra em detergente ácido não foi reduzido pela inclusão de 25,3% de caroço de algodão (5,8% de óleo) na dieta de vacas leiteiras não lactantes.…”
Section: Methodsunclassified